Effect of lncRNA‐ATB/miR‐651‐3p/Yin Yang 1 pathway on trophoblast‐endothelial cell interaction networks. Issue 12 (4th May 2021) - Yin, Yangxue; Zhang, Jiashuo; Yu, Hongbiao; Liu, Min; Zheng, Xuelian; Zhou, Rong
Abstract: Our previous studies have confirmed that lncRNA‐ATB may be involved in the pathogenesis of preeclampsia, however, it is uncertain whether lncRNA‐ATB influence the interaction between trophoblast and endothelial cells, which is crucial to the uterine spiral artery remodelling. Scratch wound healing and transwell invasion assay were conducted to test the migration and invasion of trophoblast cells. Co‐culture model was used to simulate the physiological environment in vivo. The expression levels of lncRNA‐ATB were analyzed in placenta tissues from healthy pregnant women and preeclampsia patients. Subsequently, the binding site of lncRNA‐ATB and miR‐651‐3p was verified using dual‐luciferase reporter assay, and the rescue experiment was used to study the effects of these two on the biological function. The direct effects of miR‐651‐3p and Yin Yang 1 (YY1) were verified using similar methods. LncRNA‐ATB was found to be down‐regulated in the placenta of preeclampsia patients. LncRNA‐ATB knockdown decreased trophoblast migration, invasion and colocalisation with human umbilical vein endothelial cells. MiR‐651‐3p was a direct target of lncRNA‐ATB and they had opposite effects. Moreover, the expression of lncRNA‐ATB and miR‐651‐3p in placental tissues was negatively correlated. MiR‐651‐3p has been confirmed to directly target the 3′ untranslated region of YY1. The inhibitory effects of YY1 low expression on biological function was rescued by miR‐651‐3p depletion. Western blot analysis showed that lncRNA‐ATB could regulate YY1 expression by sponging miR‐651‐3p. LncRNA‐ATB functioned as a competitive endogenous RNA of miR‐651‐3p to regulate YY1 on progress of spiral artery remodelling.